Improvement of scaffold cryopreservation by use of magnetic nanoparticles - Leal-Marin, Sara; Höltje, Kai; Lopera, Alex; Garcia, Claudia; Glasmacher, Birgit; Gryshkov, Oleksandr (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):303